Ghana [in Strategies and priorities for African agriculture] - Breisinger, Clemens; Diao, Xinshen; Thurlow, James; Benin, Samuel; Kolavalli, Shashidhara (International Food Policy Research Institute, 2012)
Ghana has experienced persistent growth with a record of positive per capita gross domestic product (GDP) growth over the past 26 years. As a result, the country is bound to become the first Sub-Saharan African country to achieve the first Millennium Development Goal (MDG1) of halving poverty and hunger ahead of the target year 2015. Underlying this success are the country’s significant efforts to build institutions and state capacity. Ghana has become a stable democratic state, as demonstrated in a peaceful transition of power in two consecutive free and fair elections in 2000 and 2008. Governance indicators have been steadily improving over the past years, and in 2007 Ghana ranked ahead of regional averages of Asia, Latin America, and Africa in most important governance indicators, including government effectiveness, regulatory quality, and control of corruption (Kaufmann, Kraay, and Mastruzzi 2009). The country is ranked among the top 10 African countries in terms of freedom of the press and academic freedom (Freedom House 2008).